Analisis Variasi Parameter Pengelasan Spot Welding Terhadap Kekuatan Tarik Pada Material SUS 304 dan DIN 1.4003 - Berlyan Putri Anugrah Nillahi Ts.; Pranowo Sidi; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Spot welding technique is one of the most important parts in the train manufacturing process, especially in the plate working stage for the train carbody. This research aims to see the parameters that affect the tensile strength of the spot welding results using the Taguchi Method on SUS 304 2 mm and DIN 1.4003 3 mm welding joints. The parameter variations performed in this Taguchi Method are current strength, welding time, and electrode diameter. While the control level used is 2 levels on Strong Current 10.5 kA and 11 kA, Welding Time 20 cycles and 25 cycles, and Electrode Diameter 6.5 mm and 12 mm. The results obtained after analyzing and processing the data are the most influential parameters, namely strong current, followed by welding time, and the smallest influence is the electrode diameter. The results of the optimum parameter combination in this study are Current Strength 11 kA, Welding Time 25 cycles, and Electrode Diameter 11 mm. The combination of these parameters has been proven in confirmation of experiments with the Taguchi Method at a confidence level of 95% in the interval of confirmation experiments.